2017
DOI: 10.2147/copd.s152826
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors predict frequent hospitalization in patients with acute exacerbation of COPD

Abstract: PurposeCOPD is a heterogeneous disease, and the available prognostic indexes are therefore limited. This study aimed to identify the factors associated with acute exacerbation leading to hospitalization.Patients and methodsThis was a retrospective study of consecutive patients with COPD (meeting the Global Initiative for Chronic Obstructive Lung Disease [GOLD] diagnostic criteria) hospitalized at the Ninth Hospital of Xi’an Affiliated Hospital of Xi’an Jiaotong University between October 2014 and September 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
2
23
0
4
Order By: Relevance
“…In our study, frequent exacerbations were highly associated with multiples admissions. This is in accordance with several other reports [4] [18]. Santibanez et al concluded in their study to the fact that a prior history of hospitalized exacerbations of COPD was associated with new admission for AECOPD with a statistically significant dose-response association.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, frequent exacerbations were highly associated with multiples admissions. This is in accordance with several other reports [4] [18]. Santibanez et al concluded in their study to the fact that a prior history of hospitalized exacerbations of COPD was associated with new admission for AECOPD with a statistically significant dose-response association.…”
Section: Discussionsupporting
confidence: 92%
“…Garcia Aymerich et al get 63% as a rate of readmission during a mean period of follow-up of 1.1 years [5]. A lower rate of 45% of readmission in one year after discharge was found in the study of Wei et al [4]. In our study, only 26% COPD patients had a mean number of hospitalizations per year more than 2.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Imaging examinations were performed using a 64-detector CT scanner (SOMATOM Definition AS, Siemens, Erlangen, Germany) with subjects holding their breath at full inspiration in the supine position. Technical parameters were based on our prior study [ 13 ] .…”
Section: Methodsmentioning
confidence: 99%
“…All CT images were automatically analyzed using the FACT-Digital Lung software [ 14 , 15 ]. The percentage of the wall area (%WA) of different generations of bronchi in each lobe, the extent of emphysema in the whole lung, right lung, left lung, and emphysema heterogeneity index (HI) were expressed according to our prior study [ 13 , 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%